PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CO-OP CO-OP UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V-D SD NEGERI 163 PEKANBARU - Yuli Handayani; Lazim N Lazim N; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was carried out because of the lowlearning outcomes of social studies of grade V-D in SD Negeri 163 Pekanbaru, KKM that is 72. The class consist of 30 students, who reached the KKM is just 14 students (46.67%), whereas students who have not yet reached the KKM is 16 students (53.33%) with average rating of class 59.83. To solve these problems then the researchers implement co-op co-op cooperative learning model. The purpose of this research is to improve the learning achievement of social studies with the implementation of the co-op co-op cooperative learning model. The result of this research shows that the average value of basic score is 59.83 and increased in cycle I from 22.59% become 73.52. In cycle II, the average value of the students also increase 33.47% become 79.86. On a basic score of students classical success criteria of social studies is 46.67%. After implementation of scramble cooperative learning model on cycle 1, number of success criteria of students classical learning increased become 66.67%. And on cycle II, success criteria of students classical learning increased by 90%. Then, the activity of the teacher on the first meeting of the cycle 1 got was 70.83% by category is enough. The second meeting was increased become 79.16% with category of good. on the first meeting of the cycle II teacher activity increased become 837.5% by category of very good. At the second meeting increased become 95.83% with the very good category. The activity of the students at the first meeting of the cycle I got was 66.66% by category of enough. The second meeting was increased become 75% with category of enough. At the first meeting of the cycle II activity of students increased become 83.33% with category of good. At the second meeting increased become 91.66% by very good category. From this research it can be concluded that by implementation of the co-op co-op cooperative learning model can improve students learning outcomes of social studies of grade V-D in SD Negeri 163 Pekanbaru.Keywords: Co-op co-op Cooperative Type, Social Studies Outcomes